Сказать - не сказать...: рассказы и повести / Виктория Токарева - Токарева Виктория Самойловна (Азбука, 2015)
Экземпляры: ф.12 (20151014) / Инвентарный номер: 56639 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 51 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44